시민참여형 공모전을 활용한 민간기록물 수집 활성화 방안: 전주 시민기록관의 기록물 수집공모전 사례를 중심으로 - 김영선; 오효정; 이정은; Kim, YoungSeon; Oh, Hyo-Jung; Lee, Jung-eun (Journal of Records Management & Archives Society of Korea, 2021)
The recent revision of the Public Records Management Act provided a basis for the procurement of private records from local archives. Accordingly, some local governments are promptly trying to gather these private records through various ways, and a representative methodology of such is a contest for acquiring records. This study aims to analyze how much this contest contributes to the acquisition of private records and the current status of its operation. As an example of this study, Jeonju Citizens Archives, which conducted the contest more than ten times, was selected. Based on the analysis results, the operation status of the contest for acquiring records and improvement plans for activation were presented. 최근 공공기록물법의 개정을 통해 지방기록물관리기관에서도 민간기록물을 수집할 수 있는 근거가 마련되었다. 이에 몇몇 지방자치단체에서는 선제적으로 민간기록물을 수집하고자 하는 다양한 방법을 시도하는 바, 대표적 방법론으로 시민참여형 기록물 수집공모전을 시행하고 있다. 이에 본 연구에서는 기록물 수집공모전이 실제 민간기록물의 수집에 얼마나 기여하는지에 대한 검토와 공모전 운영현황 등을 검토하고자 한다. 이를 위해 비교적 꾸준한 수집공모전을 진행하고 있는 전주시의 시민기록관을 사례로 선정하고 실제로 수집된 기록물의 목록을 분석하였다. 분석결과를 토대로 기록관 및 공모전 운영 측면과 공모전 활성화 측면에서의 시사점과 개선방안을 제안하였다.